SOSIALISASI PENCEGAHAN BULLYING DAN CYBERBULLYING: STRATEGI MENGHADAPI ANCAMAN DI ERA DIGITAL - Fadila nur Zakina; Nurul Mukhlisah; Rahmawati; Nasrah (STKIP Subang, 2025)
Bullying and cyberbullying remain prevalent issues in elementary school environments and have negative impacts on students’ comfort as well as their psychosocial development. Students’ low level of understanding regarding the forms, impacts, and prevention of bullying and cyberbullying served as the background for the implementation of a Community Service Program (Pengabdian kepada Masyarakat/PKM) in the form of a socialization activity for fifth-grade students at SD Negeri Biringkaloro, Gowa Regency. This activity aimed to provide knowledge and foster students’ awareness in preventing and responding to bullying and cyberbullying as an implementation of the Tri Dharma of Higher Education, particularly in the community service aspect. The program was conducted collaboratively by lecturers and students of Universitas Muhammadiyah Makassar in cooperation with teachers of SD Negeri Biringkaloro through the stages of planning, implementation, and reporting, using a socialization method accompanied by interactive discussions. The results indicated that students participated enthusiastically and were actively involved in efforts to prevent bullying and cyberbullying. Therefore, this socialization activity is effective as apreventive measure in creating a safe and comfortable learning environment for students.